URGENCY OF THE CHOICE OF THE ARRANGEMENT OF THE PLATE AT NAKOSTN THE OSTEOSYNTHESIS OF FRACTURES OF THE CLAVICLE IN A AVERAGE THIRD - G. A. Airapetov; N. V. Zagorodniy; A. A. Volna; A. A. Vorotnikov; I. P. Ponomarev; E. A. Konovalov; P. V. Portnova; M. S. Zimoglyadova (Кубанский научный медицинский вестник)
Research of 42 patients with the closed changes of a diaphysis of a clavicle to which at a nakostny osteosynthesis plates in 22 cases on the top surface of a clavicle were established, and in 20 - on a forward surface is carried out. The rentgenografiya method is used, and also the analysis of value judgment is carried out by the patients of own condition. The plate arrangement on a forward surface of a clavicle led to decrease in number of complications, increase of stability and durability of fixing of a change.